Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian pada Distro One Thing - Faijan Fahrula; Ita Purnama; Muhajirin (Teewan Journal Solutions, 2026)
This study aims to examine the influence of product quality and price on purchasing decisions at the One Thing distribution center. This study used a quantitative method with multiple linear regression analysis. The population in this study were all users of One Thing distribution centers. The sample used in this study was purposive sampling, with a sample size of 96 respondents who had used One Thing distribution centers. The results showed a positive and significant influence of product quality on purchasing decisions, and a positive and significant influence of price on purchasing decisions. Therefore, it can be concluded that product quality and price simultaneously influence purchasing decisions.